Faktor-Faktor yang Berhubungan dengan Pelaksanaan Dokumentasi Asuhan Keperawatan Berbasis Komputer - Sianturi, Sondang Ratnauli; Afriana, Denny; Lina, Rosa Nora (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2024)
Documentation is an important part of nursing care as it is one of many essential functions of a nurse that known to affect nursing care service quality given to the patients. The following research is aimed to know factors that are related to computer-based documentation of nursing care. This research is a quantitative research with descriptive correlation design and cross-sectional approach. 121 nurses as respondents were obtained with purposive technique sampling. Univariate analysis result shows that the majority of respondents’ age with 58 respondents (47.9%), the majority of level of education is Diploma III in nursing with 85 respondents (70.2%) and profession studies in nursing with 36 respondents (29.8%). Respondents who received training previously and received supervision were recorded with 95 respondents (78.5%) and 97 respondents (80.2%) respectively. Respondents with good motivation on the subject matters were recorded with 59 respondents (48.7%). The results of the Chi Square analysis test showed that there was a relationship between training (p-value ,008), supervision (p-value ,007) and motivation (p-value ,002) and there was no relationship between the age of the respondents (p-value ,983), and the level of education of the respondents (p-value ,792) with the implementation of computer-based nursing care documentation. For this reason, training, periodic supervision and motivating nurses in carrying out computer-based nursing care documentation are needed.